Cdc42 is involved in NC1 peptide‐regulated BTB dynamics through actin and microtubule cytoskeletal reorganization. Issue 12 (2nd November 2019) - Su, Wenhui; Cheng, C. Yan
Abstract : Noncollagenous domain 1 (NCl)‐peptide is a biologically active peptide derived from the C‐terminal region of collagen α3(IV) chain, a structural constituent protein at the basement membrane in the rat testis, likely via proteolytic cleavage of matrix metalloproteinase 9. Studies have shown that this NC1 peptide regulates testis function by inducing Sertoli cell blood‐testis barrier (BTB) remodeling and is also capable of inducing elongate spermatid exfoliation through its disruptive effects on the organization of actin‐ and microtubule (MT)‐based cytoskeletons at these cell adhesion sites. However, the underlying molecular mechanism remains unknown. NC1 peptide was found to exert its biologic effects through an activation of small GTPase cell division control protein 42 homolog (Cdc42) because cooverexpression of the dominant negative mutant of Cdc42 [namely, Cdc42‐T17N ( via a single mutation of amino acid residue 17 from the N terminus from Thr to Asn by site‐directed mutagenesis, making it constitutively inactive)] and NC1 peptide was able to block the NC1 peptide‐induced Sertoli cell tight junction‐permeability barrier disruption. Their cooverexpression also blocked the NC1 peptide‐induced misdistribution of BTB‐associated proteins at the cell‐cell interface and also disruptive cytoskeletal organization of F‐actin and MTs through changes in spatial expression of the corresponding actin and MT regulatory proteins. Interestingly, NC1 peptide was also found to induce an up‐regulation of phosphorylated (p)‐ribosomal protein S6 (rpS6) (namely, p‐rpS6‐S235/S236) and a concomitant down‐regulation of p‐Akt1/2 (namely, p‐Akt1‐S473 and p‐Akt2‐S474), but these changes could not be blocked by overexpression of Cdc42‐T17N. More importantly, NC1 peptide‐induced Cdc42 activation was effectively blocked by treatment of Sertoli cell epithelium with a p‐Akt1/2 activator SC79, which is also capable of blocking NC1 peptide‐induced down‐regulation of p‐Akt1‐S473 and p‐Akt2/S474, but not p‐rpS6‐S235/S236 up‐regulation. In summary, these findings illustrate that Cdc42 is working downstream of the mammalian target of rapamycin complex 1/rpS6/Akt1/2 signaling pathway to support NC1 peptide‐mediated effects on Sertoli cell function in the testis using the rat as an animal model.—Su, W., Cheng, C. Y. Cdc42 is involved in NC1 peptide‐regulated BTB dynamics through actin and microtubule cytoskeletal reorganization. FASEB J. 33, 14461‐14478 (2019). www.fasebj.org